Judo across ages: coaches’ perspectives on key elements of intergenerational training programmes - Perazzetti, Andrea; Guidotti, Flavia; Capranica, Laura; Galea, Envic; Kozsla, Tibor; Sacripanti, Attilio; Lampe, Nuša; Lampe, Špela; Spanjol, Iris; Jelušić, Toma; Bradic, Slavisa; Lascau, Maria-Loredana; et al. (Frontiers in Psychology, 2025)
IntroductionJudo is an Olympic combat sport and martial art known for promoting physical, psychological, and social wellbeing across all ages. In line with European initiatives encouraging intergenerational activities, judo presents a valuable opportunity to connect younger and older individuals through shared physical activities. Conducted within the framework of the ERASMUS+ Sport JOY Project, this study explored judo coaches’ knowledge, opinions, and experiences to identify key components for designing effective and sustainable intergenerational judo programmes.MethodA survey was distributed to 349 judo coaches (M = 82% and F = 18%) affiliated with international judo organisations and clubs to investigate their views on key characteristics, roles, barriers, and facilitators of intergenerational judo, as well as their coaching philosophies and educational needs.ResultsMain findings revealed that in such programmes coaches prioritize safety and skill ex-change while promoting social interactions. Significant differences emerged based on coaches’ demographics, experience, and education level, particularly regarding their perspectives on coaching roles, communication challenges, and motivational aspects.DiscussionFrom a psychological perspective, these programmes foster mutual respect, empathy, and intergenerational understanding, contributing to enhanced mental wellbeing and a stronger sense of belonging among participants. Indeed, the study provides essential insights to inform the creation of inclusive, engaging, and sustainable training strategies that promote active ageing, mutual learning, and social cohesion through judo.